2018
DOI: 10.3389/fphys.2018.01572
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Shift Mitochondrial Dynamics and Enhance Oxidative Phosphorylation in Recipient Cells

Abstract: Mesenchymal stem cells (MSCs) are the most commonly used cells in tissue engineering and regenerative medicine. MSCs can promote host tissue repair through several different mechanisms including donor cell engraftment, release of cell signaling factors, and the transfer of healthy organelles to the host. In the present study, we examine the specific impacts of MSCs on mitochondrial morphology and function in host tissues. Employing in vitro cell culture of inherited mitochondrial disease and an in vivo animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 83 publications
2
28
0
Order By: Relevance
“…Indeed, in their niche, MSC energy metabolism may primarily rely on anaerobic glycolysis rather than oxidative phosphorylation [ 99 ]. Our results are consistent with data shown in a high-fat diet-fed mouse model, in which MSC transplants improved mitochondrial morphology and metabolic performance in the host liver [ 100 ]. This may describe a general mechanism of MSC action, since stem cell-derived donor mitochondria increased oxidative phosphorylation and ATP generation, and reduced ROS production in host cells like, e.g., myeloma cells [ 101 ], macrophages [ 102 ], cardiomyocytes [ 103 ], and airway epithelial cells [ 104 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in their niche, MSC energy metabolism may primarily rely on anaerobic glycolysis rather than oxidative phosphorylation [ 99 ]. Our results are consistent with data shown in a high-fat diet-fed mouse model, in which MSC transplants improved mitochondrial morphology and metabolic performance in the host liver [ 100 ]. This may describe a general mechanism of MSC action, since stem cell-derived donor mitochondria increased oxidative phosphorylation and ATP generation, and reduced ROS production in host cells like, e.g., myeloma cells [ 101 ], macrophages [ 102 ], cardiomyocytes [ 103 ], and airway epithelial cells [ 104 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, under the effects of lipid peroxidation products and TNF-α on mitochondrial respiration, mitochondrial ROS oxidizes unsaturated FAs to cause lipid peroxidation. Lipid accumulation after hepatectomy can damage the ultrastructure of mitochondria and change the mitochondrial dynamics, thus reducing the activity of mitochondrial respiratory chain complex and β-oxidation function 35 . The damage of mitochondrial function further aggravates the steatosis after hepatectomy by reducing the β-oxidation of FA, forming a vicious circle, which is difficult to correct.…”
Section: Discussionmentioning
confidence: 99%
“…Reestablishment of redox balance implies preservation of the physiological and naturally produced ROS, intrinsically involved in cell signaling processes, instead of oxidative-agents ablation [ 48 ]. MSC therapy has the great potential to restitute redox state through mitochondrial modulation and anti-oxidative effects [ 49 ]. Our results indicated that MSCs induced the recovery of mitophagy-related genes PINK1 and PARKIN expressions, in addition to inducing the expression of TFAM, a gene related to the biogenesis process, which has important biological implications.…”
Section: Discussionmentioning
confidence: 99%